2016
DOI: 10.1016/j.molp.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Activates S-Type Anion Channel via OST1 and Ca 2+ Modules

Abstract: Voltage (mV) Voltage (mV) Voltage (mV) Voltage (mV) Current (pA) Current (pA) Current (pA) Current (pA) Voltage (mV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 10 publications
2
29
0
Order By: Relevance
“…At the same time, protein kinase OST1 functions in H2S-induced activated SLAC1 channel currents (Wang et al, 2016). These electrophysiological results accurately showed H2S-induced stomatal closure through numerous ions flow.…”
Section: +supporting
confidence: 55%
“…At the same time, protein kinase OST1 functions in H2S-induced activated SLAC1 channel currents (Wang et al, 2016). These electrophysiological results accurately showed H2S-induced stomatal closure through numerous ions flow.…”
Section: +supporting
confidence: 55%
“…Sulfide, a metabolite in the sulfate assimilation pathway, has been reported to induce stomatal closure (Scuffi et al, 2014;Honda et al, 2015;Wang et al, 2016). To test the requirement of functional sulfur metabolism, we analyzed whether sulfate induces stomatal closure in mutants lacking the ability to produce sulfide (sir1-1) and those unable to incorporate sulfide into Cys (serat tko).…”
Section: Sulfate Assimilation Is Essential For Sulfate-induced Stomatmentioning
confidence: 99%
“…Sulfide is primarily produced in leaves by sulfite reductase (SiR), which catalyzes the last and committed step of sulfate reduction (Khan et al, 2010). However, the mode of action of sulfate or sulfide on stomata closure has not been identified due to the dual nature of these compounds as potential signaling molecules and as part of the primary metabolic network (Scuffi et al, 2014;Honda et al, 2015;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work also showed that heat shock could improve the resistance of maize seedlings to heat, chilling, salt, and drought stress (Gong et al, 2001). Numerous studies found that the acquisition of stress tolerance including cross-adaptation was involved in a complex signal network consisting of many second messengers such as Ca 2+ , abscisic acid (ABA), hydrogen peroxide (H 2 O 2 ) and nitric oxide (NO), as well as their crosstalk (Knight, 2000; Pandey, 2015; Li and Gu, 2016; Li and Jin, 2016; Niu and Liao, 2016; Wang et al, 2016). In tobacco, mechanical stimulation can successively trigger H 2 O 2 and NO signaling (Li and Gong, 2011, 2013), heat shock can induce Ca 2+ and ABA signaling one after the other (Gong et al, 1998a,b), which in turn induce cross-adaptation to heat and chilling stress, similar results were reported by Gong et al (2001) in maize seedlings.…”
Section: Introductionmentioning
confidence: 99%